Relationship Between The Size Of The Portion Of The Diet Served And Blood Sugar Levels In Patients With Type 2 Diabetes Mellitus - Rita Juniara Kasih; Laila Apriani Hasanah Harahap; Suci Eka Putri; Teuku Muliadi (Pusat Riset dan Inovasi Nasional, 2024)
Diabetes mellitus is a chronic metabolic disorder characterized by increased blood sugar levels. Poor eating patterns, including inappropriate meal times and inappropriate amounts of food consumption, can affect blood sugar levels in the body.The aim of this research isto determine the relationship between the size of the diet portion served and blood sugar levels in Diabetes Mellitus patients at RSUD Datu Beru Kab. Central Aceh in 2023.The method used is a quantitative method,analytical observationalwith approachcross-sectional. This research was carried out from September 2023 to May 2024. The type of data is primary data obtained from the patient's general description questionnaire and data on the portion size served was obtained from direct weighing and secondary data was obtained from the patient care book, namely data on blood sugar levels 2 hours after eating. The method for collecting data is by using questionnaire sheets, checking maintenance books and eating scales. Data analysis was carried out using univariate and bivariate analysis using the Fisher exact test. The research results showed that as many as 82.0% had high kgd (>180mg/dl) and 18% had normal kgd (80-179mg/dl). There were 23.6% good portions served and 76.4% poor food portions. The results of the Fisher test show p <0.05 (0.002) and have a PR value >1 (4.2) which is a risk factor between the size of the portion served and the blood sugar levels of patients with type 2 diabetes mellitus. The conclusion is that the size of the portion served is partly The size does not match the standard portions served, causing respondents to have higher blood sugar levels 2 hours after eating. There is a significant relationship and 4 times higher risk between the size of the diet portion and blood sugar levels in patients with type 2 diabetes mellitus. Suggestions for Hospitals should improve the quality of health services, especially food services, and nutritionists/nutritionists should be able to supervise the portioning process to produce food portions that suit patient needs.